Rare predicted loss of function alleles in Bassoon (BSN) are associated with obesity - Na Zhu; Charles A. LeDuc; Ilene Fennoy; Blandine Laferrère; Claudia A. Doege; Yufeng Shen; Wendy K. Chung; Rudolph L. Leibel (npj Genomic Medicine, 2023)
Abstract Bassoon (BSN) is a component of a hetero-dimeric presynaptic cytomatrix protein that orchestrates neurotransmitter release with Piccolo (PCLO) from glutamatergic neurons throughout the brain. Heterozygous missense variants in BSN have previously been associated with neurodegenerative disorders in humans. We performed an exome-wide association analysis of ultra-rare variants in about 140,000 unrelated individuals from the UK Biobank to search for new genes associated with obesity. We found that rare heterozygous predicted loss of function (pLoF) variants in BSN are associated with higher BMI with p-value of 3.6e-12 in the UK biobank cohort. Additionally, we identified two individuals (one of whom has a de novo variant) with a heterozygous pLoF variant in a cohort of early onset or extreme obesity and report the clinical histories of these individuals with non-syndromic obesity with no history of neurobehavioral or cognitive disability. The BMI association was replicated in the All of Us whole genome sequencing data. Heterozygous pLoF BSN variants constitute a new etiology for obesity.